Management of Varicose Vein by Hirudotherapy - Iqbal, Arsheed; Quraishi, Haider Ali; Huma; Shah, Arjumad; Rashid, Adil; A, Raheem (International Journal of Scientific Research in Biological Sciences, 2019)
Varicose veins are veins that have become enlarged and twisted and are commonly found in legs. The calf muscles of the leg pumps. The venous blood back to the heart against the gravity. When the veins become varicose the valves do not function properly as the blood flows backwards and the veins engorge. The varicose veins are most common in the superficial veins of legs and due to high pressure while standing the veins engorging and ulceration can occur. Only ten percent of the venous blood in the legs is returned back by superficial veins, hence the surgical removal can be opted for superficial varicose veins. Other modalities of treatment included sclerotherapy, elastic stockings, leg elevation, exercise, radiofrequency ablation, endovascular laser treatment etc. In this study Hirudotherapy has been done at Regional Research Institute of Unani Medicine, Srinagar for the treatment of varicose vein and has been observed that leech relieves the symptoms of the varicosity by reducing the engorgements of the superficial leg veins and also improve the venous valvular functioning and thus helps to push the blood normally without regurgitation.